Le département de langue et littérature françaises de l'Université McGill de 1853 à nos jours - Lamonde, Yvan (Université McGill - Département de langue et littérature françaises, 2013)
Keywords: Langue; Université McGill

Racialized social relations in higher education: Black student and faculty experiences of a Canadian university - Hampton, Rosalind (Université McGill, 2017)
Keywords: McGill Daily; McGill, James; Noirs; Université McGill

Wisdom, Justice, and Charity: Canadian Social Welfare throught the life of Jane B. Wisdom, 1884-1975 - Morton, Suzanne (Studies in Gender and History, 2014)
Keywords: Philanthropie; Université McGill

Medical Genetics at McGill: The History of a Pioneering Research Group - Canning, Christopher; Weisz, George; Tone, Andrea; Cambrosio, Alberto (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2013)
Keywords: Médecine; Université McGill

"An Ocean of Noise": H.E. Reilley and the Making of a Legitimate Social Problem, 1911-45 - Rudy, Jarrett; Kenny, Nicolas; Fahrni, Magda (Journal of Canadian Studies / Revue d'études canadiennes, 2017)
Keywords: Physique; Université McGill

Canada's big biblical bargain: how McGill University bought the Dead Sea Scrolls - Kalman, Jason; du Toit, Jaqueline Susann (McGill-Queen's University Press, 2010)
Keywords: Théologie; Université McGill

De Freud au Père Mailloux : transmission, paradoxes et institutionnalisation : une histoire des origines de la psychanalyse au Québec - Adam-Vézina, Élodie (Université du Québec à Montréal, 2017)
Keywords: Psychologie; Université McGill; Université de Montréal

La langue de la libération / The Language of Liberation - Mills, Sean (Des actions parlantes. Aspects de la culture québécoise des années 1960 et 1970 / Actions that speaks. Aspects of Quebec Culture in the 1960s and 1970s, 2012)
Keywords: Anglophones; Francophones; Université McGill

Designing the Medical Museum - Adams, Annmarie (Healing Spaces, Modern Architecture, and the Body, 2018)
Keywords: Musées; Médecine; Université McGill

Histoire de la médecine au Québec, 1800-2000. De l'art de soigner à l'art de guérir - Goulet, Denis; Gagnon, Robert (Septentrion, 2014)
Keywords: Hôpitaux; Médecine; Université McGill; Université de Montréal

Faire l’économie du savoir. Usages et représentations du financement public des universités du Québec, de l’après-guerre à la Révolution tranquille (1950-1968) - Racine St-Jacques, Jules; Maltais, Martin (Globe: revue internationale d'études québécoises, 2014)
Keywords: Université McGill; Université Sir George Williams; Université de Montréal

L'effet des dons des entreprises privées sur les organisations-non-productrices-de-profit: le cas des universités de Montréal - Fabi, Ian (Université de Montréal, 2010)
Keywords: Philanthropie; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal

L'émergence et le développement de la discipline informatique dans les universités québécoises (1960 à 2000) - Mirabel, Philippe (Université du Québec à Montréal, 2013)
Keywords: Anglophones; Francophones; Université McGill; Université de Montréal; Université du Québec à Montréal

L’enseignement de la médecine vétérinaire au Québec 150 ans d’histoire! - Pepin, Michel (Histoire Québec, 2016)
Keywords: McEachran, Duncan McNab; Université McGill; Université de Montréal; École de médecine vétérinaire

John Wilson McConnell. Homme d'affaires, éditeur de journal, humaniste et philanthrope canadien / John Wilson McConnell: Canadian businessman, newspaper publisher, humanitarian, and philanthropist - Nieuwendyk, Dick (Héritage Dorval, 2016)
Keywords: Hommes d'affaires; McConnell, John Wilson; Montreal Star; Philanthropie; Sucre; Université McGill

Déploiement et influence de l'Église catholique montréalaise - Perron, Normand (Histoire de Montréal et de sa région, 2012)
Keywords: Communautés religieuses; Diocèse; Institut canadien; Notre-Dame (paroisse); Sulpiciens; Ultramontains; Université McGill; Université de Laval à Montréal; Églises

The Spread and Influence of the Catholic Church in Montreal - Perron, Normand (Montreal: The History of A North American City, 2018)
Keywords: Communautés religieuses; Diocèse; Institut canadien; Notre-Dame (paroisse); Sulpiciens; Ultramontains; Université McGill; Université de Laval à Montréal; Églises

L’émeute des tramways de Montréal (1955) et la mauvaise conduite des étudiants: un cas d’appropriation de l’espace urbain - Poitras, Daniel (Urban History Review / Revue d'histoire urbaine, 2018)
Keywords: Association générale des étudiants de l'Université de Montréal; Associations étudiantes; Délinquance; Tramways; Transport en commun; Université McGill; Université de Montréal; Émeutes; Étudiants

Champ culturel et espace montréalais (I): la vie culturelle à Montréal avant 1960 - Bellavance, Guy; Poirier, Christian (Histoire de Montréal et de sa région, 2012)
Keywords: Art association; Expositions; Musique; Musée McCord; Musées; Radio; Théâtre; Université McGill; Édition

Cultural Field and Montreal Space (I): Cultural Life in Montreal - Bellavance, Guy; Poirier, Christian (Montreal: The History of A North American City, 2018)
Keywords: Art association; Expositions; Musique; Musée McCord; Musées; Radio; Théâtre; Université McGill; Édition

Encountering Maude Abbott - Adams, Annmarie (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2018)
Keywords: Abbott, Maude E.; Femmes; Histoire; Hôpitaux; Musées; Médecine; Royal Victoria Hospital; Université McGill

Science et technologie à Montréal: la longue naissance d'une ville du savoir - Trépanier, Michel (Histoire de Montréal et de sa région, 2012)
Keywords: Association canadienne-française pour l'avancement des sciences (ACFAS); Avionnerie; Botanique; Chimie; Ingénieurs; Jardin botanique; Marie-Victorin, Frère; Physique; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal; École polytechnique

Science and Technology: The Coming of Age of a City of Knowledge - Trépanier, Michel (Montreal: The History of A North American City, 2018)
Keywords: Association canadienne-française pour l'avancement des sciences (ACFAS); Avionnerie; Botanique; Chimie; Ingénieurs; Jardin botanique; Marie-Victorin, Frère; Physique; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal; École polytechnique

Scolarisation, industrialisation et urbanisation au XIXe siècle - Gagnon, Robert (Histoire de Montréal et de sa région, 2012)
Keywords: Bureau des écoles protestantes; Commission des écoles catholiques de Montréal; Communautés religieuses; Enseignants; Université McGill; École normale Jacques-Cartier; École polytechnique; Écoles normales

Education in the Nineteenth Century - Gagnon, Robert (Montreal: The History of A North American City, 2018)
Keywords: Bureau des écoles protestantes; Commission des écoles catholiques de Montréal; Communautés religieuses; Enseignants; Université McGill; École normale Jacques-Cartier; École polytechnique; Écoles normales

The Well-Being of Kenyan-Canadian Parents and Youth Living in Mixed Families in Montreal - Williams, Alexandra (Université McGill, 2014)
Keywords: Africains; Famille

Sri Lankan Women's Career Identity Evolution after Immigration to Montreal, Quebec, Canada - De Silva, Nilmini (Université McGill, 2010)
Keywords: Femmes; Sri Lankais; Travail

Enforcing the Right to Healthy Housing: Recourse for Montreal Tenants Facing Health and Safety Problems at Home - Auchinleck, Jennifer (Université McGill, 2011)
Keywords: Locataires; Logement

Mothering Citizens: Elite Women in Montreal, 1890-1914 - Kirkland, Mary Elizabeth (Université McGill, 2012)
Cette thèse porte sur l'engagement social et politique de femmes de l'élite montréalaise de 1890 à 1914. Pour ce faire, j'ai réuni vingt Montréalaises issues des communautés anglophones, francophones, protestantes, catholiques et orthodoxes juives en une biographie collective qui lève le voile sur leur vie domestique, les rituels propres à leur classe sociale, leur travail philanthropique, de même que sur leur engagement au sein de la communauté locale et élargie. Cet exercice de style m'a permis de mettre en évidence l'influence des identités de genre, de race, d'ethnie, de classe et de religion de chacune sur sa conception de la société. La mise en commun des expériences de ces femmes de l'élite montréalaise révèle également que leurs préoccupations étaient plurielles et qu'elles dépassent la seule question du suffrage féminin. L'idéologie maternaliste embrassée par ces activistes traçait les jalons d'un futur meilleur, d'une ville assainie et d'une nation plus forte. Ma thèse est que les femmes constituant ce corpus combinaient leurs rôles de mères et leurs identités de citoyennes afin de se tailler une place, un cercle d'influence, dans des sphères d'activité qui leurs étaient habituellement défendues, soit les sphères sociale et politique. Pour y arriver, elles ont placé la famille au cœur de leur conception du système social et ont transposé cette vision à la communauté, à la nation et au monde. En tant qu'épouses, mères, mais aussi en tant que citoyennes, ces maternalistes croyaient qu'elles avaient un rôle important à jouer dans la transformation de la société. Le fait qu'elles aient partagé les mêmes identités sexuelle et sociale leur a permis de se rapprocher. Ces similarités, jumelées à leurs différences ethniques et religieuses leurs ont conféré une influence et un pouvoir indéniable à Montréal et au-delà. Les sources consultées révèlent que ces femmes de l'élite montréalaise étaient loin d'être passives ou contentes de rester dans l'ombre. Leur engagement politique et citoyen était conscient. Leur influence comportait néanmoins des limites qu'elles durent apprendre à repousser avec doigté. Avec le déclenchement de la Grande Guerre, les tensions cachées qui existaient entre elles s'aggravèrent et il ne fut bientôt plus possible de coopérer. La séparation de ce groupe eut pour résultat de diminuer de façon notoire le pouvoir et l'influence que ces femmes de l'élite montréalaise avaient acquis en près de vingt-cinq ans.
Keywords: Bourgeoisie; Femmes

Where Do I Belong? Narratives from the Lives of Iranians in Montreal - Dehghani Estarki, Mahdi (Université McGill, 2010)
Keywords: Iraniens

"Doing it for the family": Educational Experiences of First-Generation Female Filipino Teens in Public Schools in Montreal - Pineda, Stephanie June (Université McGill, 2010)
Keywords: Philippins; Étudiants

Homonormative Architecture & Queer Space: The Evolution of Gay Bars and Clubs in Montréal - Vallerand, Olivier (Université McGill, 2010)
Keywords: Alcool

Participatory and Critical Out-of-School Learning for Urban Youth: Building Community through Popular Culture - Tan, Eloise (Université McGill, 2010)
Keywords: Musique

Imported Devotions: Roman Catacomb Saints in Ultramontane Montreal - Dahan, Michel (Université McGill, 2014)
Keywords: Reliques; Ultramontains; Églises

There's No Place Like Home: Feminist Communities, Social Citizenship and (Un)Belonging in Montreal's Long Women's Movement, 1952-1992 - Ricci, Amanda (Université McGill, 2015)
Keywords: Anglophones; Autochtones; Femmes; Francophones; Féminisme; Haïtiens; Italiens; Noirs

A captivating ''Open City'': the production of Montreal as a ''wide-open-town'' and ''ville ouverte'' in the 1940s and '50s - Kuplowsky, Adam (Université McGill, 2014)
Keywords: Alcool; Criminalité; Délinquance; Prostitution

A Community of Believers and Healers: Learning from the functional characteristics of Hôtel Dieu - McDonald, Marie-Pierre (Université McGill, 2014)
Keywords: Communautés religieuses; Hôpitaux; Hôtel-Dieu

Race and beauty in Canada: print culture, retail, and the transnational flow of products, images and ideologies, 1700s to present - Thompson, Cheryl (Université McGill, 2014)
Keywords: Esclaves; Noirs

Single Room Occupancy (SRO) for Montreal’s Homeless Population - Rubial Carvajal, Isabella (Université McGill, 2016)
Keywords: Logement; Pauvreté

The Sattikka, the Turban and the Spices, the Cultural Landscape of a South Asian Neighbourhood: A Study on the Ethnic Diversity in Contemporary Montreal - Islam, Khadiza (Université McGill, 2016)
Keywords: Bengalis; Pakistanais; Parc-Extension (quartier); Quartiers; Sri Lankais

Imagining Sufism and Muslimness: the production of knowledge about Sufism and its power against political Islam in the United States, Canada, and Pakistan - Mercier-Dalphond, Geneviève (Université McGill, 2017)
Keywords: Musulmans

Bilinguefact your air: literary representations of French Canada, 1945-48 - Isler, Julia (Université McGill, 2017)
Keywords: Anglophones; Bilinguisme; Francophones; Roman

"Temple of my Heart": Understanding religious space in Montreal's Hindu Bangladeshi Community - Bhattacharjee, Aditya (Université McGill, 2017)
Keywords: Bengalis; Hindous

Blackness, exclusion, and the law in the history of Canada’s public schools, Ontario and Québec, 1850–present - Zellars, Rachel (Université McGill, 2017)
Keywords: Noirs

La poésie en langue des signes et ses usages à Montréal (1960-2017) - Daigneault, Catherine (Université McGill, 2018)
Keywords: Langue; Poésie; Sourds

The many worlds of Louis Riel: a political odyssey from Red River to Montreal and back 1840-1875 - Hamon, Max (Université McGill, 2017)
Keywords: Collège de Montréal; Communautés religieuses; Sulpiciens

Envisioning new futures: Portrait photographs of black Victorians in Montreal, 1861-1901 - Evoughlian, Sandra (Université McGill, 2018)
Keywords: Noirs; Notman, William; Photographie

Identity construction of Chinese immigrants: Exploring the processes of identity construction among Chinese immigrant parents and young adults in Montreal - Qian, Lingwei (Université McGill, 2016)
Keywords: Chinois; Quartier chinois; Quartiers

Reinforcing racial hierarchy through visual culture : black enslaved children in New France and early Quebec (1700-1834) - Trahan-Thomassin, Marilou (Université McGill, 2019)
Keywords: Enfants; Esclaves; Noirs; Peinture; Publicité